2003
DOI: 10.1002/glia.10296
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular phospholipase A2 inhibitors suppress central nervous system inflammation

Abstract: Phospholipase A2 (PLA2) plays a key role in the production of proinflammatory mediators, namely the arachidonic acid-derived eicosanoids, lysophospholipids, and platelet-activating factor, and indirectly influences the generation of cytokines, nitric oxide (NO), and free radicals. Accordingly, regulation of its activity is important in the treatment of inflammation. Since the main site of PLA2 action in inflammatory processes is the cell membrane, we synthesized extracellular PLA2 inhibitors (ExPLIs) composed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 37 publications
1
38
0
Order By: Relevance
“…store release or CRAC channel activation. In fact, AA generated by PLA 2 has been implicated in the generation of proinflammatory eicosanoids that regulate the production of cytokines, NO, and free radicals involved in the pathogenesis of immune-mediated inflammatory diseases such as multiple sclerosis (24,25). Eicosanoids are also produced by some prokaryotic and eukaryotic pathogens (26) and induce inflammation and host susceptibility to these pathogens (9).…”
Section: Discussionmentioning
confidence: 99%
“…store release or CRAC channel activation. In fact, AA generated by PLA 2 has been implicated in the generation of proinflammatory eicosanoids that regulate the production of cytokines, NO, and free radicals involved in the pathogenesis of immune-mediated inflammatory diseases such as multiple sclerosis (24,25). Eicosanoids are also produced by some prokaryotic and eukaryotic pathogens (26) and induce inflammation and host susceptibility to these pathogens (9).…”
Section: Discussionmentioning
confidence: 99%
“…PGE2 levels were determined in BAL fluid by RIA using specific antibody and a radioligand as previously described by Pinto et al (29). Anti-PGE 2 and standard PGE2 were purchased from Sigma (St. Louis, MO).…”
Section: Methodsmentioning
confidence: 99%
“…The ExPLIs, designed and synthesized in the laboratory of S. Yedgar (42), have been previously found effective in amelioration of inflammatory processes in cell cultures and in animal models. These include inhibition of lipid membrane hydrolysis by diverse types of sPLA 2 (9), inhibition of group V sPLA 2 activation in LPS-stimulated P388D macrophages (3), endotoxin-induced sepsis in rats, as expressed by reduced mortality rate, blood cytokine level (TNF-␣, IL-6), and expression of type IIA sPLA 2 and inducible nitric oxide synthase in liver and kidney of septic rats (4), suppression of sPLA 2 and PGE 2 production by LPS-stimulated cultured rat brain glial cells and experimental allergic encephalomyelitis in rats and mice (29), and trinitrobenzensulfonic acid-induced colitis in rats, expressed by reduced mortality rate, histology, and blood sPLA 2 activity (20). Using the ExPLIs, in the present study we have found that OVA-induced asthma in rats is associated with elevation of sPLA 2 and suppression of cPLA 2 activity and expression in the lung.…”
mentioning
confidence: 99%
“…21 Its production has been reported to be linked to PLA 2 produced lipid mediators 22 and was found to be inhibited by ExPLIs in lipopolysaccharide stimulated cells 23 and animals. In line with these findings, we determined the effect of ExPLI on NO production by cultured macrophages collected from BAL fluid of the different groups following their in vivo treatment without further treatment of the cultured cells.…”
Section: Effect Of Hype Inhalation On Biochemical Markersmentioning
confidence: 98%